Population structure, growth and recruitment of two exploited infralittoral molluscs (Haliotis midae and Turbo sarmaticus) along the south east coast, South Africa - Proudfoot, Lee-Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2007)
The two most frequently exploited species along the south east coast of South Africa are the gastropods, Haliotis midae (abalone) and Turbo sarmaticus (alikreukel). H. midae is a high valued commercial species, and suffers intense levels of illegal fishing. T. sarmaticus however, has no commercial value but is the preferred food item for impoverished subsistence communities. Owing to the fact that no legal commercial fishery exists for either species along the south coast, very few studies have been undertaken, especially in the heavily exploited infralittoral. Infralittoral size frequency distributions for both species revealed significant variation in density and size among sites of varying exploitation pressure. Densities ranged between 0 "“ 2.23 mâ »Â² (H. midae) and 0.03 "“ 4.93 mâ »Â² (T. sarmaticus) and maximum shell lengths ranged from 49.4 "“ 153.5 mm (H. midae) and 28.3 "“ 104.4 mm (T. sarmaticus). Relatively high densities and large sizes were found in marine reserves and secluded areas, and low densities and small sizes at sites near to large population centres and within the former Ciskei homeland region. Mean size of the largest 10% of the population, total density and sexually mature density were significantly related to exploitation predictors for both species. In addition, densities of H. midae juveniles were significantly related to exploitation predictors, suggesting that recruitment may be suppressed at the most exploited sites. Exploitation of T. sarmaticus tended to be localized with refuge and subtidal populations persisting. H. midae exploitation was however, far more extensive and intense. Growth of H. midae was investigated using three methods; mark-recapture, cohort analysis and growth banding analysis at Kowie Rocks, Port Alfred. The most useful of these methods for determining growth was a new technique described for growth banding analysis; which was validated using cohort analysis and measurements of shells of known age. This technique was less time consuming and labour intensive than previously described methods. Abalone growth was best described by the Schnute (1981) growth function. Systematic geographic variation in growth was observed for 10 sites along the South African coastline. Significant differences in growth among sites existed for animals between 0-4 years (P < 0.0001) and 4-6 years (P < 0.0001), and in the mean maximum sizes attained (P < 0.001). In general, abalone from the south east/east coast were found to have faster growth rates, smaller mean maximum sizes and attained sexual maturity earlier than those along the south west/ west coast. Haliotis midae recruit and juvenile densities were found to differ significantly among sites of varying exploitation pressure (P < 0.0001) and among months for recruit densities (P < 0.001). Exploited sites had low recruit and juvenile densities compared to unexploited sites and peak recruitment occurred during October/ November 2005. Recruit densities were significantly related to infralittoral adult densities during two of the three sampling months (P<0.05), when recruitment was low. No relationship was observed during the period of high recruitment, with all sites receiving high recruit densities. It was concluded that variation in recruit densities was the result of a combination of both density-dependent relationships (i.e. local spawner density and temporal variability in recruitment intensity) and the possible dispersal capabilities of H. midae. In addition, it was concluded that at present recruitment overfishing was not occurring along the south east coast. Post-recruitment mortality rates were variable but relatively constant, with hypothetical percentage survival and density curves revealing high rates and similar mortality curves among sites. Variation in juvenile densities was consequently a result of initial recruit densities and not variation in post-recruitment mortality. T. sarmaticus populations were found to be regionally sustainable and persisted along the south east coast due to adjacent intertidal and subtidal refuge populations. However, H. midae populations are becoming decimated along the south east coast. From the information obtained in this study new management proposals were suggested and discussed, such as closed areas and region-based management fisheries together with stock enhancement. These suggestions may prove to be feasible alternatives to present management strategies.
Keywords: Abalones -- South Africa; Abalones -- Growth -- South Africa; Turbinidae -- South Africa; Mollusks -- South Africa